Using relational contract principles to construe the landlord-tenant relationship: Some preliminary observations - Villiers, L.; Webb, Eileen (Thomson Reuters, 2011)
Can the understanding and interpretation of leases be enhanced by relationalcontract considerations? In this article the authors explore the pertinence ofrelational contract theory, particularly in relation to retail leases. The articleoutlines the nature of leases, the contractualisation process and the influenceof certain statutes on leasing transactions. It then focuses on relationalcontract theory and the extent to which different types of leases may beregarded as relational. The main focus of the article is on retail leases;considering the terms of the lease “contract” but also examining whetherrelational analysis may inform the interpretation of statutes relevant to retailleasing transactions.